GOKHRU (TRIBULUS TERRESTRIS AND PEDALIUM MUREX): MEDICINAL IMPORTANCE OF CHOTA GOKHRU AND BADA GOKHRU IN AYURVEDA AND MODERN SCIENCE - CHOUDHARY, SHAILJA; KAURAV, HEMLATA; CHAUDHARY, GITIKA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Tribulus terrestris and Pedalium murex are the two popular herbal plants originated from a very famous Ayurvedic plant named Gokshuru. These plants are well known for their medicinal importance. In Ayurveda, T. terrestris is known as laghu gokhshuru and P. murex is known as brihat gokshuru. The fruits of T. terrestris plant are slightly astringent in taste while the fruits of P. murex are somewhat sweeter in taste. The fruits are used to treat various diseases such as urinary disorder adrenal stone. In this current paper, we have discussed the pharmacological, Ayurvedic and folk uses of these plants in every region of the world. From various reported studies, it was found that the T. terrestris plant carries much medicinal importance while the P. murex fruits is only used as a substitute or as an adulterant of the T. terrestris plant. It was found that the T. terrestris plant is mainly used to cure urinogenital disorders and kidney disorders such as renal and gall bladder stone. On the other hand, the P. murex plant carries aphrodisiac property and mainly used to cure sexual disorders like infertility, erectile dysfunctioning in both male and females. It was also found that these plants have some similar phytochemical constituents which possess aphrodisiac, anti-inflammatory, demulcent, diuretic properties, and also used to cure other diseases such as cough, asthma, cardiac disease, vesical calculi, and gall bladder stone. These plants are known for major therapeutic properties such as anti-ulcerative, antiurolithic, anticancer, aphrodisiac, analgesic, stomachic, anti-hypertensive, diuretic, urinary anti-infective, cardio tonic, antibacterial, anti-inflammatory, nephroprotective, antispasmodic, anthelmintic, and anti-carcinogenic.